Examining the effects of competitive state anxiety and goal orientation on sports performance of college track and field athletes - Ziwei Wu; Ziwei Wu; Feng Luo; Xu Liu; Junhua Li; Yin Zhou; Jie Luo (Frontiers in Psychology)
Existing studies on athletes’ sports performance (SP) have identified significant associations between competitive state anxiety (CSA) and goal orientation (GO). However, few studies have explored the intrinsic relationships among CSA, GO, and SP. Moreover, there is a lack of attention paid to college track and field (T&F) athletes as a specific group, particularly regarding the role of GO in this process. We investigated the relationship between CSA and GO as well as their effects on athletes’ SP using a sample of Chinese college T&F athletes (N = 87, 44.8% female). Specifically, the mediating role of GO in the relationship between CSA and SP was examined. Task orientation significantly mediated the relationship between self-confidence and SP, with higher levels of task orientation leading to shorter completion times for the 1500-meter race. However, ego orientation was not associated with sports performance. These findings suggest that fostering task orientation and enhancing self-confidence are crucial to improving SP. This study deepens our understanding of CSA and GO in athletes by contributing to the current theoretical framework. Furthermore, our results offer practical recommendations for coaches and educators to develop evidence-based training strategies aimed at optimizing athletes’ psychological and sports performance.